Using Active Patterns for the Conceptual Design of Self-Optimizing Systems Exemplified by an Air Gap Adjustment System - Gausemeier, Jürgen; Dangelmaier, Wilhelm; Zimmer, Detmar; Schmidt, Alexander; Frank, Ursula; Klöpper, Benjamin (Computers and Information in Engineering Conference, Parts A and B)

Conceptual Design of Self-Optimizing Systems Exemplified by a Magnetic Linear Drive - Gausemeier, Jürgen; Zimmer, Detmar; Frank, Ursula; Pook, Sebastian; Schmidt, Alexander (International Conference of Engineering Design)

Messung von radialen Lagerkräften an einem CVT-Variator mit Schubgliederband - Zimmer, Detmar; Möller, Jens (VDI-Gesellschaft Entwicklung Konstruktion Vertrieb (VDI-EKV))

Messung der radialen Lagerkräfte eines CVT-Variators - Zimmer, Detmar; Felgenhauer, Benedikt; Möller, Jens (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Konzipierung selbstoptimierender Systeme am Beispiel eines magnetischen Linearantriebs - Gausemeier, Jürgen; Frank, Ursula; Pook, Sebastian; Zimmer, Detmar; Schmidt, Alexander

Dimensioning and tolerancing in international comparison. Confrontation of standardisation works of GPS and GD&T - Denzer, Vera (CIRP Conference on Computer Aided Tolerancing. Specification and Verification for Assemblies)

Untersuchungen zur Verformung, zum Lauf des Umschlingungsmittels und zur Reibung in einem stufenlosen Umschlingungsgetriebe - Felgenhauer, Benedikt

Modelling and Identification of an All-Terrain Vehicle - Bruns, Torsten; Schäfer, Erika (International Journal of Vehicle Systems Modelling and Testing 2007)

RailCab - Ein Schienenverkehrssystem mit autonomen, Linearmotor getriebenen Einzelfahrzeugen - Henke, Christian; Rustemeier, Carsten; Schneider, Tobias; Böcker, Joachim; Trächtler, Ansgar (Internationaler ETG - Kongress 2007)

Self-Calibration of the 6-dof Parallel Robot TriPlanar by Identification of the Geometry Parameters - Cinkaya, Hueseyin; Noelle, Rene; Münch, Eckehard; Trächtler, Ansgar (AIM 2007)

X-by-Wire Test Vehicle for the Test of New Design Methods and Tools to Interconnect Vehicle-Dynamics Control Systems - Nachtigal, Vitalij; Trächtler, Ansgar; Jäker, Karl-Peter (5th IFAC Symposium on Advances in Automotive Control (AAC))

Optimal Control Inputs to Affect Vehicle Dynamics in Various Driving States - Salfeld, Maike; Stabrey, Stephan; Trächtler, Ansgar (5th IFAC Symposium on Advances in Automotive Control (AAC))

Modellierung des Papiertransports in Geldautomaten - Just, Viktor; Trächtler, Ansgar; Jäker, Karl-Peter (Mechatronik 2007)

Selbstkalibrierung des 6 DOF Parallelroboters TRIPLANAR durch Identifikation der Geometrieparameter mit einem einfachen Messverfahren - Cinkaya, Hueseyin; Münch, Eckehard; Noelle, Rene; Trächtler, Ansgar; Toepper, S. (Mechatronik 2007: Innovative Produktentwicklung)

Tool Support for Developing Advanced Mechatronic Systems: Integrating the Fujaba Real-Time Tool Suite with CAMeL-View - Burmester, Sven; Giese, Holger; Henkler, Stefan; Hirsch, Martin; Tichy, Matthias; Gambuzza, Alfonso; Münch, Eckehard; Voecking, Henner (29th International Conference on Software Engineering (ICSE))

Modellbasierter Entwurf mechatronischer Fahrwerksysteme - Trächtler, Ansgar (Paderborner Workshop Entwurf Mechatronischer Systeme (EMS))

Potenziale und Risiken der Selbstoptimierung für die Verlässlichkeit mechatronischer Systeme - Frank, Ursula; Giese, Holger; Müller, Thomas; Oberthür, Simon; Romaus, Christoph; Tichy, Matthias; Voecking, Henner (Paderborner Workshop Entwurf Mechatronischer Systeme (EMS))

Realisierung eines Werkzeuges zur algorithmischen Differenzierung von Modellen mechatronischer Systeme - Münch, Eckehard; Cinkaya, Hueseyin; Trächtler, Ansgar (Paderborner Workshop Entwurf Mechatronischer Systeme (EMS))

Analysis of the Vehicle Dynamics and Yaw Moment Maximization in Skid Maneuvers - Salfeld, Maike; Stabrey, Stephan; Trächtler, Ansgar (chassis.tech 2007)

Ein plattformunabhängiges Softwaretool für die schnelle Qualitätskontrolle von Transmissions- und dynamischen Emissionsdaten in der PET - Krevert, B.; Dang, T. B.; Weise, R.; Fricke, H.; Domik, Gitta; Buchert, W. (45. Jahrestagung der DGN)

Can ISPs and P2P users cooperate for improved performance? - Aggarwal, Vinay; Feldmann, Anja; Scheideler, Christian (ACM Computer Commucation Review)

Modellierung der Hysterese- und Adhäsionseffekte zwischen Bremsbelag und Bremsscheibe - Tonchev, Anton; Hirschberg, Wolfgang; Sextro, Walter; Major, Zoltan; Neges, Josef (27. Internationales Mju-Symposium/Bremsen-Fachtagung)

Modelling of Hysteresis and Adhesion Effects between Brake Pad and Disc - Tonchev, Anton; Hirschberg, Wolfgang; Sextro, Walter; Major, Zoltan; Neges, Josef (27. Internationales Mju-Symposium/Bremsen-Fachtagung)

Non-destructive ultrasonic test of orange dehydration - Camarena Gandia, Francisco; Hemsel, Tobias; Espinosa, Victor; Twiefel, Jens; Ardid, Miquel; Martinez-Mora, Joan; Gandia, Joan Babtiste (Proceedings of 19th international congress on Acoustics, Madrid)
Penetration tests (Magness-Taylor, force/deformation, Kramer multiblade shear) applied directly over the peel of the fruit are the most acceptable methods for measuring firmness and turgidity of fruits and vegetables [1, 2]. To replace these destructive and mechanical penetration methods by non-destructive ultrasonic measurements implies a great advance in order to obtain fast studies about the state of the fruit at the time of harvest, during storage, and in the distribution points. Moreover, there are other advantages since this technique can be fast, non-destructive, fully automated, and performed on-line [1]. Within this context, the objective of this study was to examine the relationship between physico-mechanical characteristics (oil-gland break stress, thickness and dehydration) and ultrasonic characteristics in the ``Salustiana'' orange peel during the complete dehydration process of the orange at ambient conditions. After a description of the measurement system [3], the fruit selection procedure and the measurement protocol, we analyze the results of the change of physico-mechanical and ultrasonic properties in the orange peel and their change with storage time.

Schwingungsverhalten elastischer Körper mit nichtlinearen Kopplungen in ausgedehnten Reibkontakten - Genzo, Alexander; Sextro, Walter; Panning, Lars (VDI-Berichte)

Resonant vibrating sensors for tactile tissue differentiation - Hemsel, Tobias; Stroop, Ralf; Oliva Uribe, David; Wallaschek, Jörg (Journal of Sound and Vibration)
Surgical resection of brain tumours is a difficult task. To enhance surgery results, a tactile sensor is wanted that gives better resolution and sensitivity than the human tactile sense. The characteristics of resonant vibrating piezoelectric elements change with varying load. This allows for calculation of mechanical load parameters by measuring electrical quantities. Different setups of piezoelectric sensors have been used to investigate soft materials. Finally, a piezoelectric bimorph sensor gave good results for distinguishing tissue mimicking gel-phantoms with different gelatine concentrations.

Perspectives of Tumour Therapy by Local Ultrasonic Hyperthermia and Thermal Ablation - Lierke, Ernst-Günter; Hemsel, Tobias (Proceedings of 19th international congress on Acoustics, Madrid)

Fundamental Study on A Thickness-Shear Transformer using X-Cut Lithium Niobate - Shigematsu , Takashi; Morita, Takeshi; Hemsel, Tobias (Proceedings of Symposium on Ultrasonic Electronics)

On Nonlinear Forced Vibration of Shrouded Turbine Blades - Szwedowicz, J; Visser, R; Sextro, Walter; Masserey, P. A (Journal of Turbomachinery)
Numerical predictions of the forced vibration of a disk assembly including frictional effects between the shrouds are presented concerning engineering needs for the blade design process. Assuming a tuned disk assembly, numerical static, free, and then forced vibration analyses of a shrouded turbine blade measured in the spin pit are performed systematically. For the excitation forces of an air jet evaluated from the fairly linear behavior of the experimental blade resonance peaks, the reliability of the proposed approach is validated through the very close agreement of the computed and measured resonant peaks. These resonant peaks demonstrate either a fairly linear behavior or a nonlinear one like the jump effect of blade resonance amplitudes, or elastic impacts between the shrouds. Also, the damping performance for different contact configurations between the shrouds is numerically analyzed. These numerical results indicate that the shrouds generate higher frictional damping for small angles (0â30deg) between the circumferential direction and the normal vector to the contact surface.

Proceedings of the 10th International Conference on Model Driven Engineering Languages and Systems (MoDELS 2007), Nashville, TN (USA)

Proceedings of the MoDELS 2007 Workshop on Model Driven Development of Advanced User Interfaces (MDDAUI '07), Nashville, Tennessee (USA)

A Model-Based Approach for Platform-Independent Binary Components with Precise Timing and Fine-Grained Concurrency - Schattkowsky, Tim; Engels, Gregor; Förster, Alexander (Proceedings of the 40th Annual Hawaii International Conference on System Sciences (HICSS 2007))

Generation of Business Process Models for Object Life Cycle Compliance - Küster, Jochen; Ryndina, Ksenia; Gall, Harald (Proceedings of the conference on Business Process Management (BPM 2007), Brisbane (Australia))

Model Driven Development of Advanced User Interfaces (MDDAUI) - MDDAUI'06 Workshop Report - Pleuß, Andreas; Van den Bergh, Jan; Sauer, Stefan; Hußmann, Heinrich; Bödcher, Alexander (MoDELS 2006 Workshops)

Easy Model-Driven Development of Multimedia User Interfaces with GuiBuilder - Sauer, Stefan; Engels, Gregor (Proceeding of the 4th International Conference on Universal Access in Human-Computer Interaction (UAHCI, as Part of HCI International, 2007), Beijing (China))
GUI builder tools are widely used in practice to develop the user interface of software systems. Typically they are visual programming tools that support direct-manipulative assembling of the user interface components. We have developed the tool GuiBuilder which follows a model-driven approach to the development of graphical (multimedia) user interfaces. This allows a meta-design approach where user interface developers as well as prospective users of the system are supported in modelling the desired functionality of the GUI on a high level of abstraction that is easy to understand for all involved stakeholders. The model consists of compositional presentation diagrams to model the structure of the user interface and hierarchical statechart diagrams to model its behaviour. GuiBuilder then supports the transformation of the model to Java, i.e., the generation of a working user interface and the simulation of the modelled behaviour. Interactive sessions with the user interface can be recorded and replayed.

ClassSheets - model-based, object-oriented design of spreadsheet applications - Bals, Jan-Christopher; Christ, Fabian; Engels, Gregor; Erwig, Martin (Proceedings of the TOOLS Europe Conference (TOOLS 2007), Zürich (Swiss))

KnowledgeBus - An Architecture to Support Intelligent and Flexible Knowledge Management - Mlynarski, Michael; Hinkelmann, Knut; Magenheim, Johannes; Nelkner, Tobias; Reinhardt, Wolfgang; Holzweissig, Kai (Creating New Learning Experiences on a Global Scale, Second European Conference on Technology Enhanced Learning, EC-TEL 2007, Crete, Greece, September 17-20, 2007)

Verification of Business Process Quality Constraints Based on Visual Process Patterns - Förster, Alexander; Engels, Gregor; Schattkowsky, Tim; Van Der Straeten, Ragnhild (Proceedings of the First Joint IEEE/IFIP Symposium on Theoretical Aspects of Software Engineering (TASE 2007), Shanghai (China))

Structuring Software Cities - A Multidimensional Approach - Hess, Andreas; Humm, Bernhard; Voß, Markus; Engels, Gregor (Proceedings of the 11th IEEE International Enterprise Distributed Object Computing Conference (EDOC 2007))

Vom Informations- zum Wissensmanagement: Der Knowledge Bus als flexibler Lösungsansatz - Mlynarski, Michael; Nelkner, Tobias; Reinhardt, Wolfgang (Informatiktage 2007: Fachwissenschaftlicher Informatik-Kongress, 30. und 31. März 2007, B-IT Bonn-Aachen International Center for Information Technology Bonn)

Improving Inconsistency Resolution with Side-effect Evaluation and Costs - Küster, Jochen; Ryndina, Ksenia; Gall, Harald (Proceedings of the ACM/IEEE 10th International Conference on Model Driven Engineering Languages and Systems (MODELS 2007), Nashville, TN (USA))

Generation of Business Process Models for Object Life Cycle Compliance - Ryndina, Ksenia; Küster, Jochen; Gall, Harald (Proceedings of the BPM Demonstration Program (satellite event of the 5th International Conference on Business Process Management (BPM 2007)), Brisbane (Australia))

Smart Teams: Simulating Large Robotic Swarms in Vast Environments - Arens, Stephan; Buss, Alexander; Deck, Helena; Dynia, Miroslaw; Fischer, Matthias; Hagedorn, Holger; Isaak, Peter; Kutylowski, Jaroslaw; Meyer auf der Heide, Friedhelm; Nesterow, Viktor; Ogiermann, Adrian; Stobbe, Boris; et al. (Proceedings of the 4th International Symposium on Autonomous Minirobots for Research and Edutainment)
We consider the problem of exploring an unknown environment using a swarm of autonomous robots with collective behavior emerging from their local rules. Each robot has only a very restricted view on the environment which makes cooperation difficult. We introduce a software system which is capable of simulating a large number of such robots (e.g. 1000) on highly complex terrains with millions of obstacles. Its main purpose is to easily integrate and evaluate any kind of algorithm for controlling the robot behavior. The simulation may be observed in real-time via a visualization that displays both the individual and the collective progress of the robots. We present the system design, its main features and underlying concepts.

Reusable Architectural Decision Models for Enterprise Application Development - Zimmermann, Olaf; Gschwind, Thomas; Küster, Jochen; Leymann, Frank; Schuster, Nelly (Proceedings the conference on Quality of Software-Architectures (QoSA 2007), Medford, MA (USA))

"Modelchecking" - Eine Methode zur Verbesserung der Softwarequalität - Gehrke, Matthias; Güldali, Baris; Kindler, Ekkart

Investigation of multicast-based mobility support in all-IP cellular networks - Festag, Andreas; Karl, Holger; Wolisz, Adam (Wireless Communications and Mobile Computing)

WASP - Wirelessly Accessible Sensor Populations: A Project Overview - van der Stok, Peter; Karl, Holger; De Ambroggi, Fabio; Decotignie, JeanDominique; Siegemund, Frank; Lokhorst, Kees; Hellenschmidt, Michael (Constructing Ambient Intelligence - AmI 2007 Workshops Darmstadt, Germany, November 7-10, 2007 Revised Papers)

Outage probability analysis of cooperative transmission protocols without and with network coding: inter-user channels based comparison - H. Woldegebreal, Dereje; Valentin, Stefan; Karl, Holger (Proceedings of the 10th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2007, Chania, Crete Island, Greece, October 22-26, 2007)

Traffic-Aware Asymmetric Cooperation Diversity for Media Streaming in Wireless Networks - Valentin, Stefan; von Malm, Holger; Karl, Holger (Proceedings of the IEEE 18th International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2007, 3-7 September 2007, Athens, Greece)

Integrating multiuser dynamic OFDMA into IEEE 802.11a and prototyping it on a real-time software-defined radio testbed - S. Lichte, Hermann; Valentin, Stefan; Eitzen, Falk; Stege, Matthias; Unger, Carsten; Karl, Holger (3rd International ICST Conference on Testbeds and Research Infrastructures for the Development of Networks and Communities, TridentCom 2007, Orlando, Florida, USA, May 21-23 2007)

Finanzwirtschaftliche Analyse der schenkungsteuerlichen Zehnjahresregel - Kundisch, Dennis; Pfeiler, F.; Schiefele, V. (Steuer und Wirtschaft)

MuPAD: eine Einführung - Rapin, Gerd; Wassong, Thomas; Wiedmann, Stefan; Koospal, Stefan
Keywords: mupad

Graphentheoretische Konzepte in der Gymnasialen Oberstufe: Ein Unterrichtsentwurf unter Berücksichtigung der Neuen Medien - Wassong, Thomas

Customer Portfolio Management in E-Commerce – A Risk Management Perspective - Kundisch, Dennis; Sackmann, S.; Ruch, M. (INFORMS International Puerto Rico 2007 Meeting)

Außerbörslicher Emittentenhandel: Handelsplatzwahl von Online-Investoren - Kundisch, Dennis; Stuber, T. (Wirtschaftsinformatik 2007 - eOrganisation: Service-, Prozess-, Market-Engineering)

Bank controlling using Basel II-data: Are internal approaches dispensable? - Kundisch, Dennis; Loehner, F.; Rudolph, D.; Steudner, M.; Weiss, C. (2007 Enterprise Risk Management Symposium Monograph)

Spezifizierung des Kano-Modells zur Messung von Kundenzufriedenheit - Buhl, H. U.; Kundisch, Dennis; Schackmann, N.; Renz, A. (Wirtschaftsinformatik 2007 - eOrganisation: Service-, Prozess-, Market-Engineering)

Feedbackgespräche: Überstrapaziert, missverstanden und bedeutungslos? Ganz im Gegenteil: Best Practise bei der Deutschen Bahn - Terlinde, P; Giardini, A; Kabst, Rüdiger; Halbach, J; Pelchrzim, H

Strategische Personalentwicklung: Wenn dem Bildungscontroller die Ziele fehlen - Giardini, A; Kabst, Rüdiger

Funktionale Äquivalente zur Personalplanung : Eine empirische Studie zur Personalplanung klein- und mittelständischer Unternehmen auf Basis des Cranet - Matiaske, W; Holtmann, D; Kabst, Rüdiger (Planung in kleinen und mittleren Unternehmen, Jahrbuch der KMU-Forschung und -Praxis 2007)

Leistungsbeurteilung und -vergütung in der privaten Wirtschaft und im öffentlichen Dienst: Eine vergleichende Betrachtung auf Basis des „Cranfield-Projects“ 1995-2005 - Giardini, A; Kabst, Rüdiger (Leistungsvergütung im Öffentlichen Dienst)

Preventing E-mail Spam: The Conceptualization and the Analysis of an Infrastructure Framework - Schryen, Guido
Spamming remains a form of Internet abuse, which burdens the Internet infrastructure, is generally regarded as an annoyance, and is said to cause a huge economic harm. Many technological, organizational, and legislative anti-spam measures have already been proposed and implemented, but have not led to any substantial decrease in the number of spam e-mails. We propose a scalable and flexible infrastructure framework that integrates several anti-spam measures and that features both a technological and an organizational facet. The key element of our infrastructure is a new organizational unit that reliably and transparently limits the number of e-mails that can be sent per day and per account. We also analyze the proposed framework in terms of its theoretical effectiveness, the required resources, and its limitations.
Keywords: Email; Infrastructure; Internet; Spam

Joint Venture Performance: A Meta-Analysis - Isidor, R; Hornung, F; Kabst, Rüdiger

Pre-and post entry learning of young technology firms: antecedents of objective and tacit knowledge and performance implications - Schwens, C; Kabst, Rüdiger

Self-Organization in Sensor and Actor Networks - Dressler, Falko
Self-organization is a rather fascinating concept that enables systems consisting of huge numbers of autonomously acting subsystems to perform a collective task. Moreover, self- organizing systems show an overall behavior that cannot easily be predicted or even preprogrammed in a scalable way. It was in the early 1960ies that people like Ashby and Eigen investigated self-organization properties in (natural) systems. Since these days, a great number of (technical) solutions have been developed, which, either on purpose or unintentionally, inherently the basic concepts of self-organization. The aim of this book is to investigate the concepts of self-organization in the context of autonomous sensor and actor networks. The primary objective is to categorize the basic self-organization methods and to survey techniques for communication and coordination in massively distributed systems according to the developed classification scheme. Basically, two possible approaches can be thought of for organizing this book. First, we could start analyzing sensor and actor network technology and figure out what basic mechanisms are employed and how these relate to self-organization. A second approach would be to introduce self-organization as a methodology, apparently used everywhere in our life (in nature and in technical systems), and afterwards to continue with technical issues in sensor and actor networks searching for previously learned self-organization methods. I decided to follow the second approach in order to keep the focus on self-organization while studying the term in the world of sensor and actor networks. The term self-organization is still often misunderstood and misinterpreted. Therefore, this textbook is intended to be a basis for a better understanding of the concepts of self-organization, especially in the domain of sensor and actor networks. It provides a stepwise introduction of definitions, methodologies, and corresponding techniques relevant in the context of self-organization. Recent advances in miniaturization and wireless communication enabled the development of low-cost sensor nodes. Additionally, new application domains of sensor and actor networks emerged that demand for huge numbers of interacting devices. Thus, the relevance of self-organization methods is rapidly increasing as it is considered the primary control paradigm for distributed and massively distributed systems. The reader will see that self-organization has a number of advantages compared to other control paradigms. So, it becomes possible to operate huge numbers of collaborating subsystems even in case of limited resources, unreliable communication, and in case of massive failures of single systems. Unfortunately, these advantages are accompanied by some rather annoying side effects such as the increasing complexity and a nondeterministic behavior. By using optimal combinations of the basic methods of self-organization, these disadvantages can be minimized to some extent. According to the objective of this textbook - to study sensor and actor networks - the most relevant domains of communication and coordination are deeply investigated based on well-known algorithms and mechanisms and a number of case studies. This includes networking aspects of medium access control, ad hoc routing, data-centric communication, and clustering techniques. Additionally, control mechanisms for cooperation, task and resource allocation, and collaborative actuation are investigated. The book is concluded by a brief introduction of the domain of bio-inspired algorithms. This study is included for two reasons. First, to demystify the term bio-inspired networking, and secondly, to show the capabilities of such bio-inspired approaches.

Einsatz von E-Portfolios zur Förderung von studentischen Lerngemeinschaften im Hochschulstudium. - Sporer, Thomas; Jenert, Tobias; Strehl, Bernhard; Noack, Patrick Ole (DeLFI Workshops)
Keywords: E-Portfolios; Lerngemeinschaften; Praxisgemeinschaften; Projektgruppen; Hochschulstudium; informelles Lernen

Learning about innovation and knowledge creation in higher education. - Sporer, Thomas; Jenert, Tobias; Reinmann, Gabi (4. Konferenz Professionelles Wissensmanagement - Erfahrungen und Visionen)

Semivirtuelle Lernumgebung zum wissenschaftlichen Arbeiten als Ergänzung des Studienangebots der Universität Augsburg - Heinze, Nina; Sporer, Thomas; Jenert, Tobias (Deutsche Gesellschaft für Informationswissenschaft und Informationspraxis: Tagungen der Deutschen Gesellschaft für Informationswissenschaft und Informationspraxis)
Keywords: Wissenschaftliches Arbeiten; Blended Learning; Tutoring

Student Learning Communities in the Project-Centered Study Program" Problem-Solving Competencies" - Sporer, Thomas; Heinze, Nina; Jenert, Tobias; Reinmann, Gabi
Keywords: Problem Solving Competencies; E-Portfolio

Begleitstudium Problemlösekompetenz (Version 2.0). Infrastruktur für studentische Projekte an Hochschulen - Sporer, Thomas; Reinmann, Gabi; Jenert, Tobias; Hofhues, Sandra (Studieren neu erfinden - Hochschule neu denken)

Fallstudie: Social Software im Hochschulstudium - Sporer, Thomas; Jenert, Tobias (Enterprise 2.0 - Planung, Einführung und erfolgreicher Einsatz von Social Software im Unternehmen)

p-Shell Rabi-flopping and single photon emission in an InGaAs/GaAs quantum dot - Ester, P.; Lackmann, L.; Hübner, M.C.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Bichler, M. (Physica E: Low-dimensional Systems and Nanostructures)
Very clean single photon emission from a single InGaAs/GaAs quantum dot is demonstrated by the use of a coherent optical state preparation. We present a concept for single photon emission, which uses p-shell Rabi-flopping followed by a sequence of relaxation and recombination. The proof of the (clean) single photon emission is performed by photon correlation measurements.
Keywords: Antibunching; Single photon emission; Rabi oscillation; Coherent manipulation

On the asymptotic variance in nonparametric regression with fractional time-series errors - Feng, Yuanhua (Journal of Nonparametric Statistics)

Modelling financial time series with SEMIFAR GARCH model - Feng, Yuanhua; Beran, J.; Yu, K. (IMA Journal of Management Mathematics)

Semiparametric Modeling of Stochastic and Deterministic Trends and Fractional Stationarity - Beran, Jan; Feng, Yuanhua; Franke, Günter; Hess, Dieter; Ocker, Dirk (Processes with Long-Range Correlations)

Local Polynomial Estimation with a FARIMA-GARCH Error Process - Beran, Jan; Feng, Yuanhua (Bernoulli)

Special Issue: Quantile Regression

Kundenbindung durch Weiterempfehlung? Eine experimentelle Untersuchung der Wirkung positiver Kundenempfehlungen auf die Bindung des Empfehlenden. - Eggert, Andreas; Helm, Sabrina; Garnefeld, Ina (Marketing ZfP)

Immigration policy and the labor market: the German experience and lessons for Europe - Zimmermann, Klaus F; Bonin, Holger; Fahr, Rene; Hinte, Holger

On the inverse relationship between unemployment and absenteeism: evidence from natural experiments and worker heterogeneity - Fahr, Rene; Frick, Bernd

Incentives to invest in the human capital of temporary agency workers - Schmidt, Stephanie; Thommes, Kirsten (German Journal of Human Resource Management)

Outsourcing HR functions. Development of an explanatory approach to firms'(non-existent) demand for personnel services - Alewell, Dorothea; Bähring, Katrin; Canis, Anne; Hauff, Sven; Thommes, Kirsten (Management Revue)

Kooperation und Konkurrenz in Personaldienstleistungsbeziehungen - Bähring, Katrin; Thommes, Kirsten (Kooperation und Konkurrenz)

Paderborner Forschungs- und Entwicklungswerkstatt - Forschungsfragen und -konzepte der beruflichen Bildung

Lernen in medienbasierten kooperativen Lernumgebungen - Modellversuch KooL

Qualifizierung von Berufs- und Wirtschaftspädagogen zwischen Professionalisierung und Polyvalenz - Kremer, H.-Hugo; Tramm, T. (bwp@ Berufs- und Wirtschaftspädagogik - online)

Mentoring-Modell Paderborn - Konzept und erste Erfahrungen - Burda, A.; Kremer, H.-Hugo; Pferdt, F. G. (Zeitschrift für Hochschulentwicklung)

Selbstgesteuertes Lernen in medienbasierten kooperativen Lernumgebungen - Kremer, H.-Hugo (Lernen in medienbasierten kooperativen Lernumgebungen - Modellversuch KooL)

Kooperative Lernaufgaben als Instrumente der Curriculumentwicklung - Kremer, H.-Hugo (Lernen in medienbasierten kooperativen Lernumgebungen - Modellversuch KooL)

Structural and Behavioural Compatibility of Graphical Service Specifications - Heckel, Reiko; Cherchago, Alexey (Logic and Algebraic Programming)

Software-Qualität - überall! - Excel-lente Software - Bals, Jan-Christopher; Christ, Fabian; Engels, Gregor; Sauer, Stefan (Forschungsforum Paderborn)

A Model-Driven Approach to Discovery, Testing and Monitoring of Web Services - Lohmann, Marc; Mariani, Leonardo; Heckel, Reiko (Test and Analysis of Web Services)
Service-oriented computing is distinguished by its use of dynamic discovery and binding for the integration of services at runtime. This poses a challenge for testing, in particular, of the interaction between services. We propose a model-driven solution to address this challenge. Service descriptions are promoted from largely syntactical to behavioural specifications of services in terms of contracts (pre-conditions and effects of operations), expressed in a visual UML-like notion. Through mappings to semantic web languages and the Java Modeling Language (JML) contracts support the automatic discovery of services as well as the derivation of test cases and their execution and monitoring. We discuss an extended life cycle model for services based on the model-driven approach and illustrate its application using a model of a hotel reservation service.

Architectural Style-based Modeling and Simulation of Middleware for Mobile Systems - Guo, Ping
Today, mobility is one of the most important market and technology trend within information and communication technology. As the demand for rapid deployment of dependable mobile applications increases, middleware for mobile systems is emerging as one of the most active areas of system research in mobility. The middleware is a set of distributed software services that exists between distributed operating systems and mobile applications. The key to the middleware is to provide support across the mobile application domains, help application developers overcome the complexity and problems brought by mobility, and enhance dependability and usability of developed mobile applications. The criticality and pervasiveness of middleware for mobile systems is continually growing. However, the design and development of the middleware are difficult tasks, and it is not easy to ensure the quality of a developed middleware. This is mainly caused by the increasing complexity of the middleware. In addition, the great diversity of this area makes it very difficult for the designers to reuse the already established design knowledge or successful experience when building new systems. All these make the design process quite inefficient and unpredictable, and therefore risking the project. “One man’s magic is another man’s engineering”. Engineering design is much more routine than innovative. Founding on this fundamental notion in software engineering, we develop an architectural style-based approach to deal with the problems in the thesis. We build architectural styles for a class of related middleware. The style represents a common form of design, which originates from the results that practitioners have achieved in one area. The style is formulated to repeat successes and avoid failures from previous projects. When building a new middleware, the designers and developers do not need to explore all possible alternatives for its supported architecture. Instead, they can use the architectural style that is effective for the middleware. They can define the design as instances of the style, or they can use the style as a reference model for further improvement and development. By structuring the design space for a family of related middleware, the style can drastically simplify the process of building a middleware, reduce costs of implementation through reusable infrastructure, and improve system integrity through style-specific analysis and checks. We develop the approach based on UML-like meta modeling and graph transformation techniques to support sound methodological principles, powerful modeling, formal analysis and refinement. The approach consists of several main parts: the modeling language that supports specification of the style and mobility, the refinement formalization that ensures that an abstract style is correctly refined to a concrete one, as well as the consistency check framework that validates behavioral consistency between two styles on different abstract layers. With the Fujaba simulation tool support, we also develop a style-based engineering process that helps us to efficiently develop correct and consistent styles. Besides, it allows a seamless integration of our approach into the well-known object oriented design. By providing a concrete example of how to construct the style for a class of related middleware, and how to use the style to help the design and development of a new middleware, we show that the architectural style-based approach is useful and practical.

Constructing an Emblematic Northern Space. The New Brighton Photographs of Martin Parr and Tom Wood - Tönnies, Merle (Spatial Practices 2)

Quantum dots as tunable scatterers for 2D- and 1D-electron systems - Marquardt, Bastian; Russ, Marco; Lorke, Axel; Meier, Cedrik; Reuter, Dirk; Wieck, Andreas D. (Physica E: Low-dimensional Systems and Nanostructures)

Silicon nanoparticles: Absorption, emission, and the nature of the electronic bandgap - Meier, Cedrik; Gondorf, Andreas; Lüttjohann, Stephan; Lorke, Axel; Wiggers, Hartmut (Journal of Applied Physics)

Technique for tilting GaAs photonic crystal nanocavities out of plane - Meier, Cedrik; Hennessy, Kevin (Applied Physics Letters)

Temperature-induced crossover between bright and dark exciton emission in silicon nanoparticles - Lüttjohann, S; Meier, Cedrik; Offer, M; Lorke, A; Wiggers, H (Europhysics Letters (EPL))

Effect of User Mobility in Coded Cooperative Systems with Joint Partner and Cooperation Level Selection - Valentin, Stefan; Karl, Holger (IEEE Wireless Communications and Networking Conference, WCNC 2007, Hong Kong, China, 11-15 March, 2007)

Multi-rate Relaying for Performance Improvement in IEEE 802.11 WLANs - Marie Feeney, Laura; Cetin, Bilge; Hollos, Daniel; Kubisch, Martin; Mengesha, Seble; Karl, Holger (Wired/Wireless Internet Communications, 5th International Conference, WWIC 2007, Coimbra, Portugal, May 23-25, 2007, Proceedings)